(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة خلال عامي 2001-2000 على جنس الخوخ Prunus,L. استخدمت فيها القياسات الحيوية على 19 صفة لأجزاء النبات من الورقة حتى البذرة للتمييز بين العينات التي أخذت من عدة مجموعات موزعة على موقعين في منطقتي جبلة والقدموس التابعتين لمحافظتي اللاذقية وطرطوس, وبنتيجة تحليل التباين عند المستوى %5 لمعرفة الفروق بين الصفات الكمية والنوعية المدروسة تبين وجود أربعة أنواع وطرز من الجنس Prunus,L. منتشرة في مواقع الدراسة, هذه الأنواع والطرز يمكن الإستفادة منها مستقبلا˝ في الغذاء والدواء وبرنامج التحسين الوراثي لبعض أصناف اللوزيات أو إستخدامها كأصول للتطعيم عليها . This study was executed during 2000-2001 on prunus,L. genus. Biological measurements were used on 19 features of plant portion starting from leaf till seed, in order to differentiate between samples taken from many groups which were distributed on 2 stations in Gpla & Alkdmos regions (Lattakia and Tartous districtes) . Analysis of variance (5 % level) was used to test the difference between qualitative and quantitative features. It was found that 4 differet kinds and types of the prunus,L. genus distributed in the studied station, can be utilized in food & drugs in future genetic improvement programs of some amygdalus varieties and as rootstocks.